Analysis of Political Communication of Women Candidates in the 2019 Legislative Elections in Batam City - Suryani, Suryani; Budianto, Heri (International Journal of Social and Management Studies, 2023)
This study aims to find out about political communication carried out by women candidates and the obstacles faced in the 2019 Legislative Elections in Batam City by using an element of political communication approach according to Dan Nimmo, namely political communicators, political messages, political media, political targets, effects of political communication.With proper political communication, it is hoped that the electability of women candidates in the upcoming legislative elections can increase. This research was conducted from January 2022 to early February 2023. This research uses a qualitative approach and a constructivism paradigm with case studies describing the elements of political communication carried out by female candidates. Data collection techniques were carried out by in-depth interviews with key informants. Determination of key informants with the criteria of women candidates who get a minimum of 1000 votes. Data collection techniques through interviews and documentation stages.The results of the study revealed the elements of communication used by women candidates to get voters’ votes. Political communicators are legislative candidates, campaign teams, party officials, journalists, consultants, volunteers, cadres, community leaders, traditional leaders, religious leaders. The political messages conveyed are rhetoric, political advertisements and propaganda. The political channel is through face-to-face meetings, and uses print and online media. The political targets of women candidates are rational, critical and traditional voters. The effect of the political communication of women candidates is political participation and voting in elections. Women candidates face challenges in the form of multiple roles in the household, patriarchal culture, money politics and election administration issues.